2020
DOI: 10.3390/ijms21155227
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Nucleotides Selectively Induce Migration of Chondrocytes and Expression of Type II Collagen

Abstract: The migration of chondrocytes from healthy to injured tissues is one of the most important challenges during cartilage repair. Additionally, maintenance of the chondrogenic phenotype remains another limitation, especially during monolayer culture in vitro. Using both the differentiated and undifferentiated chondrogenic ATDC5 cell line, we showed that extracellular nucleotides are able to increase the migration rate of chondrocytes without affecting their chondrogenic phenotype. We checked the potency of natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…S2). Chondrocyte’s migration ability is also known to be essential for cartilage repair [ 36 ]. We found that chondrocytes did not migrate in BM condition at the time point monitored (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2). Chondrocyte’s migration ability is also known to be essential for cartilage repair [ 36 ]. We found that chondrocytes did not migrate in BM condition at the time point monitored (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of P2X7R with BBG alleviated the cardiac fibrosis induced by TAC operation in vivo ( Zhou et al, 2020 ). Zheng et al investigated the role of P2Y1R in norepinephrine (NE)-stimulated cardiac fibroblasts, revealed that P2Y1R modulates CFs proliferation via induction of c-fos and inhibition of DNA synthesis ( Zheng et al, 1998 ; Szustak and Gendaszewska-Darmach, 2020 ). In addition, another study reported that A1, A2A, P2Y1R, P2Y11R and P2X7R agonists modulated the TGF-β1-evoked epithelial to mesenchymal transition (EMT) through the PKA and MAPK/ERK signaling pathway ( Zuccarini et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…E.g., muscarinic receptors display voltage-dependent responses, with depolarizing stimuli enhancing M1-type receptor responses while reducing those of M2 receptors ( Ben-Chaim et al, 2006 ); in chondrocytes, this may lead to increased GAG synthesis ( Lind et al, 1998 ). The ubiquitous P2Y 12 purinergic receptor, present in chondrocytes and involved in their migration ( Szustak and Gendaszewska-Darmach, 2020 ) is another example where voltage sensing through GPCRs may impact function ( Zhang et al, 2020 ).…”
Section: Making Sense Of the Streaming Potential: The Whodunit Of Mem...mentioning
confidence: 99%